Hubungan Lama Terapi ARV Dengan Kadar Viral Load pada Pasien ODHA - Adiyono Fadhil Munasir; Yustiana Arie Suwanto; Nurul Ummi Rofiah; Ahmad Muhyi (Jurnal Kesehatan Amanah, 2026)
HIV (Human Immunodeficiency Virus) is a virus that attacks the immune system. Viral load is a key indicator in monitoring HIV, where higher viral load indicates a worsening condition in the patient and can lead to the progression of the disease to AIDS (Acquired Immunodeficiency Syndrome). Viral load can also predict the likelihood of opportunistic infections, which are the leading causes of morbidity and mortality in individuals with HIV and AIDS. Objective: To analyze the relationship between the duration of ARV therapy and viral load in PLWHA at RSUP Dr. Kariadi Semarang in 2025. Results: The Spearman correlation test (rₛ = -0.405; p = 0.002) shows a significant negative correlation between the duration of ARV therapy and viral load in PLWHA. The longer the patient undergoes ARV therapy, the lower the viral load. Among patients who have undergone therapy for more than 12 months, 80.43% had an undetectable viral load, while in the 6–12 month therapy group, only 33.33% had an undetectable viral load. Conclusion: There is a significant relationship between the duration of ARV therapy and viral load. Longer ARV therapy tends to lower viral load in PLWHA. Further research is needed to understand the factors that influence viral load and the effectiveness of ARV therapy.